Perlawanan Perempuan Bugis dalam Kumpulan Cerita Pendek Ketika Saatnya karya Darmawati Majid - Ahmad Abdul Karim; Dian Hartati (Faculty of Languages and Arts, Universitas Negeri Padang, 2022)
This research is motivated by the massive dominance of Bugis men over all kinds of problems in the life of the Bugis people, including the lives of women. This controlling influence has turned Bugis women into number two beings in the social process. And Bugis women have to accept the fact that patriarchal culture is growing prolifically, including in literary texts. The purpose of this research is to discuss the efforts of the Bugis women's resistance which is contained in a collection of short stories When ItTime 'sby Darmawati Majid. The research method used is descriptive qualitative. The literature review uses an existentialist feminism approach from Simone de Beaviour. Data collection techniques used are literature study and reading and note-taking techniques. The presentation of the results is narrated in the form of descriptive analysis. The female characters carry out resistance, including resistance to marriage, resistance to tradition, and resistance social. The marginalization of female characters is caused by the stereotype of women, the subordination of women, and violence against women which diminish the existence of Bugis women.